Development and Validation of a Reading and Numeracy Literacy Asessment Instrument on Stoichiometry Using LMS - Anugrance Citra Rahma Setiyani; Triannisa Rahmawati; Nahadi Nahadi; Wiwi Siswaningsih (JURNAL PENDIDIKAN MIPA, 2026)
According to PISA results, Indonesian students' reading and numeracy skills remain low. Therefore, a quality assessment tool is needed to evaluate students' reading and numeracy skills, especially in stoichiometry. The purpose of this study was to determine an appropriate instrument for assessment. The research method used was test design and development, as outlined in the Standards for Educational and Psychological Testing. The results showed that the instrument had adequate characteristics in content validation, empirical validity, reliability, difficulty level, and discriminatory power, with most falling into the good category. Therefore, this instrument can be used as an assessment to obtain evidence of the instrument's validity and psychometric characteristics. Further research is recommended to evaluate students' levels of critical thinking, reading literacy, and numeracy. In addition, the instrument can be tested on a more diverse sample and in more schools, expanding it to other chemistry materials.